Faktor yang Berhubungan Dengan Kepatuhan Pengobatan Tuberkulosis pada Peserta JKN di FKTP Provinsi Jawa Tengah Tahun 2024 (Berdasarkan Data Sampel BPJS Kesehatan Tahun 2025) - Syela Ayunda Natasya; Fitri Indrawati; Intan Zainafree (KOLONI, 2026)
The tuberculosis treatment success rate in Central Java reached 85.9% in 2024. This figure represents a decrease from the 2023 rate of 87.8% and has not yet met the 2025–2029 strategic plan target of 90%. TB patients can achieve a full recovery if they undergo regular treatment for 6 months. Adherence to TB treatment is crucial to achieving treatment success, controlling transmission, and preventing drug resistance. This study aims to analyze and describe the determinants of TB treatment adherence at FKTP among JKN participants in Jawa Tengah in 2024 based on 2025 BPJS Kesehatan sample data. This study employed an analytical observational design with a quantitative approach and a cross-sectional design utilizing secondary data from the 2025 tuberculosis contextual BPJS Kesehatan sample data. The sample was selected using total sampling adjusted according to predefined inclusion and exclusion criteria, resulting in a sample size of 240 participants with outpatient treatment outcomes. The result of study found that 64.6% of participants adhered to TB treatment. The proportion of TB treatment utilization FKTP in Jawa Tengah with outpatient treatment outcomes was dominated by adult participants, males, the PBI segment, active participants, Class III patients, participants residing in regency areas, and participants diagnosed with pulmonary TB. The results of the chi-square test showed that participant segmentation is a variable associated with TB treatment adherence, with a p-value of 0.015. These findings underscore the importance of further policies and interventions to improve TB treatment adherence among non-PBI participants.